Evaluation of beach response due to construction of submerged detached breakwater - Lim, Changbin; Kim, Jinhoon; Kim, Jong-Beom; Lee, Jung-Lyul (Frontiers in Marine Science, 2024)
Submerged detached breakwaters (SDBWs) have increasingly been used in recent times as an alternative against their emergent counterpart (EDBWs) to mitigate erosion because the former do not spoil the seascape. Both of these structures are (usually) constructed using precast concrete blocks or natural granite rocks, hence becoming permeable structures. For an EDBW, a parabolic bay shape equation can be readily used to estimate the planar shape of the shoreline behind the structure, but there is still no approach to estimate how the shoreline behind the SDBW is formed. In this study, we estimated how the shoreline is balanced by examining how the dominant wave direction changes due to the diffraction of the transmitted wave generated after the installation of the SDBW from the long-term wave directional spectrum. The change in dominant wave direction was determined under the shoreline gradient condition where littoral drift does not occur, considering the diffraction phenomenon due to the difference in transmitted waves. This means that the shape of the equilibrium shoreline changes to face perpendicular to the dominant wave direction. As a meaningful result, when the transmittance is 0, it converges to the well-known empirical equation of EDBW. The present methodology is validated by comparing the observed data (wave and shoreline change) from two beaches (Anmok and Bongpo-Cheonjin Beaches) on the eastern coast of Korea. This rational approach to shoreline changes behind permeable SDBWs will help in proactive review work for coastal management as well as beach erosion mitigation.